Polarized Raman spectroscopy of aligned CNT fibres - Tay, Sean Meng Fai. (2012)
In recent years, the advancement and progress in the field of carbon nanotechnology has allowed for the creation of stronger and more lasting Carbon Nano-Tube (CNT) fibres. These CNT fibres are commonly used in the structural, electrical, chemical, mechanical and medical industries due to their exceptional thermal conductivity, mechanical, electrical properties and chemical inertness.